The Night Visitor, or How Pushkin Parodied Shakespeare - Szczukin, Wasilij (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper discusses the poem Count Null by Alexander Pushkin in an intertextual perspective. A comparison is made with texts which served Pushkin as sources – Titus Livy’s History of Rome and Shakespeare’s poem The Rape of Lucrece (1594). The author emphasizes original and innovative features of Pushkin’s parody of the English poet.